Spontaneous bleeding of thoracoacromial artery mimicking tunneled cuffed catheter-related complication: A case report. Issue 13 (March 2019) - Nam, Mann Hua; Tsai, Ming-Hsien; Fang, Yu-Wei; Lin, Mi-Chu
Abstract: Rationale: The chronic complications caused by the tunneled cuffed catheter in chronic dialysis patients are infection and catheter dysfunction. While bleeding due to this access can occur occasionally. Patient concerns: We present a 92-year-old woman with a 6-year history of regular hemodialysis (HD). For the past 2 years, she has been receiving HD via a tunneled cuffed catheter placed in the right internal jugular vein. She suffered from a right chest subcutaneous hematoma near the catheter without recent trauma. The increasing size of hematoma after dialysis, and the oozing from the outlet of the catheter were also observed. Diagnosis: Computed tomography of chest and angiography were done and showed that the hematoma was caused by thoracoacromial artery bleeding, which was near the puncture site of the tunneled cuffed catheter. Interventions: Fluid resuscitation, blood transfusion, surgical drainage, and parenteral antibiotics were prescribed. Outcomes: Patient recovered fully without any further sequelae. Lessons: Spontaneous bleeding of thoracoacromial artery is rare and clinicians should keep in mind as a differential diagnosis in patient with new-onset hematoma over anterior chest wall. Early diagnosis and treatment are important in such cases.